Age-Specific Features of the Enzymatic Proliferation Markers upon the Cancer of Different Localisations - Berta G. Borzenko; Elena M. Bakurova; Kseniia A. Mironova; Ulia D. Tursunova (Highlights on Medicine and Medical Research Vol. 10, 2021)
A comparative study of enzyme activity features of thymidilate "salvage pathway" synthesis and adenosine catabolism in blood serum and cancer tissues from solid adjacent tumors of different localizations was carried out. Aim: To evaluate both the diagnostic relevance of thymidilate metabolism enzymes and adenosine deaminase (ADA) activity and their association with tumor growth. Methods: The determinations of enzymes activity were examined blood serum and lymphocytes of 169 patients by the radioisotope method and spectrophotometrically. Results: We revealed that in case of cancer development the thymidine phosphorylase activity in blood serum is lower as compared to healthy persons. It was accompanied by of thymidine kinase (TK) and adenosine deaminase (ADA) activity increasing. It was shown that enzymes activity features were correlated with age and stage of disease. The enzymes activity changes depended on the efficacy of chemotherapy and eradication of the tumor. The lymphocytes ADA activity features can be the useful marker of its dysfunction. Conclusion: Our findings suggest that study of individual dynamics of the enzymes activity in blood serum may be used as informative tests for disease recurrence diagnostic and drug treatment optimization.